A Neuro-Integrative Assessment of Perceptual-Motor Performance and Wellness in ROTC Cadets. Issue 2 (April 2022) - Wilkerson, Gary B.; Colston, Marisa A.; Grillo, Ashley N.; Rogers, Abigail J.; Perry, Tyler; Acocello, Shellie N.
Resting heart rate variability (HRV) may be a useful index of both brain-based executive function and general health. Our purpose in this study was to quantify relationships among HRV, perceptual-motor performance metrics, and wellness survey responses. A cohort of 32 male Reserve Officer Training Corp (ROTC) cadets completed a dual-task upper extremity reaction time (UERT) test, two tests of whole-body reactive agility, and a 10-item wellness survey that produced a 0–100 Overall Wellness Index (OWI). We averaged participants' resting HRV measurements twice per week over 10 weeks to derive an intra-individual grand mean (HRV-IIGM) and over a series of days we calculated an intra-individual coefficient of variation (HRV-IICV). We used median values for the two HRV metrics (HRV-IIGM and HRV-IICV) to separate the cadets into equal-sized high and low HRV groups to form the dependent variable for logistic regression analyses. We found a significant inverse relationship between HRV-IIGM and HRV-IICV ( r = –0.723, p < .001). Differences in UERT in the left versus right visual hemifields (L–R Diff) and OWI scores were strongly related to both HRV-IIGM ≤ 4.49 and HRV-IICV ≥ 6.95%. Logistic regression models that included L–R Diff and OWI showed 71% classification accuracy for HRV-IIGM (Model χ2 [2] = 12.47, p = .002, Nagelkerke R 2 = 0.430) and 81% classification accuracy for HRV-IICV (Model χ2 [2] = 14.88, p = .001, Nagelkerke R 2 = 0.496). These findings suggest that resting HRV, perceptual-motor efficiency, and overall wellness are highly interrelated, supporting a multi-factor biopsychosocial assessment to guide the design and implementation of interventions to maximize operational effectiveness for ROTC cadets and other military personnel.